The Pengaruh Persepsi Konsumen dan Preferensi Konsumen Terhadap Keputusan Pembelian Ayam Goreng Pada Gerai Waralaba D'Besto Di Kota Pariaman - Syukrial; Yasnida, Yasnida; Septiawati, Noni (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2025)
This study aims to determine the effect of consumer perceptions and consumer preferences partially and simultaneously on the decision to purchase fried chicken ready-to-eat food at D'Besto in the city of Pariaman. This type of research is quantitative. The population in this study are all D'Besto Pariaman customers whose number is unknown. Sampling using Roscoe's theory. The sample used was 30 respondents. The data collection technique used a questionnaire, while the data analysis method used validity and reliability tests, descriptive statistics, classical assumptions (normality test, multicollinearity test and heteroscedasticity test), multiple linear regression analysis, and statistical tests (t test, F test and coefficient of determination). The results showed that the consumer perception variable had a significant effect on purchasing decisions with a value of tcount 2.163 > ttable 1.697 at a significant level of 0.040 <0.05. Consumer preferences have a significant effect on purchasing decisions with a t-count value of 3.549 > t-table 1.697 at a significant level of 0.001 <0.05. Consumer perceptions and consumer preferences simultaneously have a significant effect on the dependent variable on purchasing decisions with a value of Fcount = 86.866 > Ftable 2.92 with sig = 0.000 <0.05, with the influence of consumer perception variables and consumer preferences on purchasing decisions of 86.5%. Regression Equation Y= 0,403 + 0,312 X1 + 0,584 X2.